Language and cognition in bilinguals and multilinguals : an introduction - Groot, A. M. B. de (New York, NY ; Hove : Psychology Press, 2011)
This introductory level textbook comprehensively covers the psycholinguistic study of bilingualism and multilingualism, including traditional and brain-based approaches. Each chapter covers a key series of topics in clear, accessible language, and includes a description of the relevant methodological issues.
1. Introduction and preview -- 2. Early bilingualism and age of acquisition effects on (first and) second language learning -- 3. Late foreign vocabulary learning and lexical representation -- 4. Comprehension processes : word recognition and sentence processing -- 5. Word production and speech accents -- 6. Language control -- 7. Cognitive consequences of bilingualism and multilingualism -- 8. Bilingualism and the brain.
Includes bibliographical references (pages 461-495) and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Multilingualism -- Psychological aspects; Bilingualism -- Psychological aspects; Cognition -- Psychological aspects; Psycholinguistics; Electronic books